Reference intervals for haematology, clinical chemistry and acute phase reactants in free-ranging African elephants (Loxodonta africana) - Hooijberg, Emma Henriette (University of Pretoria, 2022)
MAST (MSc (Veterinary Science))--University of Pretoria, 2020.